Studi Implementasi E-Procurement Pada Peningkatan Peran Usaha Mikro, Kecil, dan Menengah (UMKM) di Kabupaten Malang - Sasmito, Cahyo; Suprojo, Agung; Anchieta, Yosephina (Universitas Tribhuwana Tunggadewi, 2024)
This study aims to analyze the effect of E-Procurement on increasing the role of Micro, Small, and Medium Enterprises (MSMEs) in Malang Regency, East Java Province. This study uses a quantitative method, data collected from questionnaires with MSME respondents who participated in the procurement of government goods and services in Malang Regency through E-Procurement. Data analysis was carried out using SEM-PLS with WarpPLS 7.0 software. This study found that E-Procurement has a very significant effect on increasing the role of MSMEs in Malang Regency. This system expands market access, improves operational efficiency, and increases transparency in the procurement process. In addition, the training and technical support provided help improve the capabilities of MSMEs in using this platform. E-Procurement is an effective tool to empower MSMEs, increase their participation in government procurement, and encourage local economic growth. However, there needs to be an increase in technological infrastructure, ongoing training, and strengthening policies to support MSMEs. These findings provide insights for local governments and other stakeholders in optimizing the benefits of E-Procurement for inclusive economic development.Penelitian ini bertujuan untuk menganalisis pengaruh E- Procurement terhadap peningkatan peran Usaha Mikro, Kecil, dan Menengah (UMKM) di kabupaten Malang, Provinsi Jawa Timur. Penelitian ini menggunakan metode kuantitatif, data dikumpulkan dari kuesioner UMKM yang berpartisipasi dalam pengadaan barang dan jasa pemerintah di kabupaten Malang melalui E-Procurement. Analisis data dilakukan dengan SEM-PLS dengan software WarpPLS 7.0. Penelitian ini menghasilkan bahwa E-Procurement berpengaruh sangat signifikan dalam meningkatkan peran UMKM di kabupaten Malang. Sistem ini memperluas akses pasar, meningkatkan efisiensi operasional, dan meningkatkan transparansi proses pengadaan. Selain itu, pelatihan dan dukungan teknis yang diberikan membantu meningkatkan kapabilitas UMKM dalam menggunakan platform ini. E-Procurement merupakan alat efektif untuk memberdayakan UMKM, meningkatkan partisipasi mereka dalam pengadaan pemerintah, dan mendorong pertumbuhan ekonomi lokal. Namun perlu adanya peningkatan infrastruktur teknologi, pelatihan berkelanjutan, dan penguatan kebijakan untuk mendukung UMKM. Temuan ini memberikan wawasan bagi pemerintah daerah dan pemangku kepentingan lainnya dalam mengoptimalkan manfaat E-Procurement untuk pembangunan ekonomi yang inklusif.